2019
DOI: 10.1029/2019gl083828
|View full text |Cite
|
Sign up to set email alerts
|

Attributing Greenland Warming Patterns to Regional Arctic Sea Ice Loss

Abstract: Observed and model‐projected sea ice loss enhances warming in the Arctic. We investigate to what extent warming on Greenland can be attributed to changes in the sea ice cover in different parts of the Arctic. Using Climate Model Intercomparison Project phase 5 model projections of the future, we perform multilinear regressions to separate the simulated warming on Greenland in two parts; one following global warming and one following regional sea ice changes. This reveals the magnitude and spatial pattern of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Enhanced summer melting at low elevation areas of the GrIS, as found here, is also a robust response to reduced Arctic sea ice cover (Rennermalm et al 2009;Noël et al 2014;Stroeve et al 2017;Pedersen and Christensen 2019). Liu et al (2016) argue that the primary mechanism for the increased surface melt of the GrIS is through increased LW in by atmospheric warming caused by sea ice loss.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Enhanced summer melting at low elevation areas of the GrIS, as found here, is also a robust response to reduced Arctic sea ice cover (Rennermalm et al 2009;Noël et al 2014;Stroeve et al 2017;Pedersen and Christensen 2019). Liu et al (2016) argue that the primary mechanism for the increased surface melt of the GrIS is through increased LW in by atmospheric warming caused by sea ice loss.…”
Section: Discussionsupporting
confidence: 62%
“…McIlhattan et al ( 2020 ) shows that Arctic precipitation frequency from liquid-containing clouds has increased in CESM2 with respect to CESM1 during all months of the year, and the annual mean is very high (0.642) in CESM2 compared to observations (0.129). However, the total amount of precipitation in CESM2 has not increased in comparison to CESM1.…”
Section: Discussionmentioning
confidence: 98%
“…Potentially, a combination of these dynamic and thermodynamic processes play a role in contributing to the near‐surface air temperature warming focused in the west/south edge of Greenland that is captured in both climate model and observationally‐based analyses (Screen, 2017; Ballinger et al ., 2018; Pedersen and Christensen, 2019). Of note, the local sea ice influence on air temperatures tends to be confined to low‐elevation areas due to mesoscale wind features, such as katabatic flows, that frequently prevent the penetration of turbulent heat from the local marine environment upslope past the lower ablation zone (Ballinger et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Its sea ice loss contributes the largest portion to the pan-Arctic sea ice declining trend during boreal winter and spring (Onarheim et al 2015(Onarheim et al , 2018, and it has experienced strong natural fluctuations at interannual, decadal, and longer time scales in the past decades (Onarheim and Årthun 2017). Many studies showed that the BS sea ice variability has likely exerted profound impacts on local weather and climate (Kohnemann et al 2017;Pedersen and Christensen 2019), ecosystem (Dalpadado et al 2014), Arctic commercial shipping (Eicken 2013;Smith and Stephenson 2013;Melia et al 2016;Pizzolato et al 2016;Laliberté et al 2016), fishery activities (Hollowed et al 2013;Haug et al 2017), and natural resource extraction (Jung et al 2016). Extensive studies also argued that BS sea ice change could have far-reaching influences on weather and climate in lower latitudes via altering large-scale atmospheric circulations in a way that resembles the North Atlantic Oscillation (NAO) (e.g., Cohen et al 2014;Kim et al 2014;Overland et al 2015;García-Serrano et al 2015;Kretschmer et al 2016;Sorokina et al 2016;Screen 2017;Zhang et al 2019; and many others), although this topic has been controversial (e.g., Overland et al 2016;Screen et al 2018;Blackport et al 2019;Cohen et al 2020;Peings 2019;Blackport and Screen 2020;Dai and Song 2020;Liang et al 2020).…”
Section: Introductionmentioning
confidence: 99%